Penyuluhan CTPS Kepada Siswa/i SDN 013 di Makroman Kelurahan Sindang Sari - Fikal Setiawan; Devi Yanti; Muhammad Wisnu Dwi Anggara; Azzahra Shafa Salsabila; Nur Annisa Afifah; Rusdi Rusdi; Muhammad Habibi (Abdimas Universal, 2024)
Hansd washing with Soap (CTPS) is considered the most fundamental method in preventing the spread of communicable diseases, with an effectiveness rate of 80% in addressing common infections and 45% in preventing more serious diseases. Proper hand washing can prevent various illnesses such as diarrhea, acute respiratory infections, hepatitis, typhoid, and bird flu, which often lead to fatalities in the community, especially among children. This community service aims to enhance the knowledge of fourth-grade students at SDN 013 Makroman Sindang Sari Subdistrict, Samarinda City, through the promotion of Hand washing with Soap (CTPS). The community service method employed includes demonstration-based education and measurement using the One Group Pre-test and Post-test design. The activities are conducted directly, delivered informally to the students of fourth-grade classes at SDN 013 Makroman. The results show an improvement in knowledge among students in classes IV-A and IV-B regarding CTPS behavior. The mean pre-test scores of 41.82 and 44.00 increased to 73.64 and 81.60, respectively. The (2-tailed) significance level < 0.05 indicates a significant difference between knowledge before and after the education. It is expected that the school authorities can periodically promote awareness, and families can monitor the continuity of students in adopting proper handwashing as a daily habit in accordance with the steps of CTPS.